Granulocyte and monocyte apheresis can control juvenile generalized pustular psoriasis with mutation of IL36RN. (1st October 2017) - Koike, Y.; Okubo, M.; Kiyohara, T.; Fukuchi, R.; Sato, Y.; Kuwatsuka, S.; Takeichi, T.; Akiyama, M.; Sugiura, K.; Utani, A.
Summary: Patients with deficiency of interleukin‐36 receptor antagonist (DITRA), due to mutation of IL36RN, exhibit psoriatic phenotypes, typically generalized pustular psoriasis (GPP). We report a paediatric patient with DITRA, whose cutaneous lesions varied from psoriasis vulgaris in infancy to annular pustular psoriasis with acute exacerbation to GPP at 13 years of age. Conventional systemic treatments for GPP, which include oral retinoids, ciclosporin and methotrexate, are controversial in paediatric cases, because of their adverse effects and uncertain long‐term consequences. Granulocyte monocyte apheresis, a process associated with few adverse events, promptly controlled the GPP of our paediatric patient, and has potential as a suitable alternative treatment for paediatric patients with DITRA. Abstract : What's already known about this topic? Mutation of IL36RN causes neutrophilic dermatosis, typified by generalized pustular psoriasis (GPP). Current treatments for paediatric GPP are a cause for concern, owing to their adverse effects. What does this study add? Variable psoriatic phenotypes were observed in a paediatric patient with mutation of IL36RN . The study suggests that granulocyte monocyte apheresis can be safe and effective in the treatment of paediatric patients with GPP.